2011
DOI: 10.1038/cgt.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

E10A, an adenovirus-carrying endostatin gene, dramatically increased the tumor drug concentration of metronomic chemotherapy with low-dose cisplatin in a xenograft mouse model for head and neck squamous-cell carcinoma

Abstract: Most cancer chemotherapeutic agents are administered at the maximum-tolerated dose (MTD) in short cycles with treatment breaks. However, MTD-based chemotherapies are often associated with significant toxicity and treatment breaks allow the opportunity for tumor regrowth and acquisition of chemoresistance. To minimize these drawbacks, a metronomic strategy, in which chemotherapeutics are administered at doses significantly below the MTD without treatment breaks, has been suggested by many investigators. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Data obtained in rodents have highlighted antiangiogenesis induced by LDM treatment with cisplatin as a key mechanism of its tumor-regressive effect on liver cancer [ 21 ]. Another investigation showed that LDM treatment with cisplatin reduced vessel density in a xenograft model of head and neck squamous cell carcinoma [ 22 ] and inhibited tumor growth via an antiangiogenic action in a murine model of transitional cell carcinoma [ 23 ]. The mechanism that confers low-dose cisplatin-induced antiangiogenesis, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained in rodents have highlighted antiangiogenesis induced by LDM treatment with cisplatin as a key mechanism of its tumor-regressive effect on liver cancer [ 21 ]. Another investigation showed that LDM treatment with cisplatin reduced vessel density in a xenograft model of head and neck squamous cell carcinoma [ 22 ] and inhibited tumor growth via an antiangiogenic action in a murine model of transitional cell carcinoma [ 23 ]. The mechanism that confers low-dose cisplatin-induced antiangiogenesis, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endostatin gene therapy is convenient in clinical application, and a cumbersome daily injection is no longer needed like the application of endostatin proteins. Up to date, Ad-Endo has completed its preclinical, phase I and phase II clinical trials [21-27,52,53] and started its phase III clinical trial on head and neck squamous cell carcinoma in China. However, Ad-Endo showed only a limited or moderate effect in previous clinical trials due to the limited increase in the endostatin concentration [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…When delivered to a murine head and neck cancer model, endostatin, used in conjunction with low-dose cisplatin treatment, reduced in vivo tumour growth. 19 A vaccinia virus vector armed with an endostatin-angiostatin fusion gene demonstrated superior anti-tumour efficacy for head and neck cancer in a pre-clinical study. 20 Apoptosis is a tightly regulated process of programmed cell death.…”
Section: Cytoreductive Strategiesmentioning
confidence: 99%